Traffic Noise Levels and Hearing Impairment Among Shop Keepers in a Metropolitan City – An Embedded Mixed-Method Study - Kirubakaran S; Kumar K , Manoj; Murugan , Arun (National Journal of Community Medicine, 2025)
Context: Traffic noise and its impact on shop keepers is studied less. Use of mobile application for assessing noise levels and hearing impairment might provide solution in resource poor settings. Aims: Assess hearing impairment in shop keepers of traffic busy roads. Measure the noise exposure and monitor the community noise level in that locality. Find association between noise exposure and level of hearing impairment. Methods and Material: The study design was embedded mixed method design. It had 1) quantitative phase - hearing impairment among shop keepers, noise level measurements and photographs of study locations were taken, 2) qualitative phase - narrative analysis of the photographs. Results: Among participants, mean hearWHO score was 49.71 ± 10.95 and 34 had hearing impairment. It is found people who work for more than 10 years had a higher chance of developing hearing loss than those who worked less than 5 years. Weekly averages of noise values exceeded permissible limits in all locations. Narrative analysis suggested increased vehicle density in all locations. Conclusions: Traffic noise levels are higher than permissible limits mainly contributed by vehicles with potential risk for causing hearing impairment on long term exposure.